(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2014)
The market developments kindled by liberalization and globalizationhave resulted in changes in the intermediation role of banks. The pace oftransformation has been more significant in recent times with technology actingas a catalyst. While the banking system has done fairly well in adjusting tothe new market dynamics, greater challenges lie ahead. Financial sector would beopened up for greater international competition under WTO.